CULTURE PERFORMANCES OF SPINY LOBSTER (Panulirus homarus) WITH OPTIMUM FEEDING RATE - Boby Aldo Saputra; Agus Setyawan; Supono Supono; Margie Brite; Yudha Trinoegraha Adiputra (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2022)
Spiny lobster (Panulirus homarus) is one of most fancy seafood products that able to grow from puerulus to consumption size in floating cage. Limited information regarding feeding rate of this species during cultured with fresh mangrove snail meat as a feed. This study purpose to evaluated culture performance of spiny lobster within different feeding rate level. Three feeding rate level of 10, 13 and 15%/day were used as treatments. Three floating cages with 120 individuals of pre-adult of spiny lobster was used. Sixty days of cultured periods with absolute growth, specific growth rate, feed convertion ratio and survival rate were analysed to determined culture performances. Results showed that 13%/day of feeding rate was supported highest absolute growth and specific growth rate. It is showed different performances with 10%/day and 15%/day of feeding rate. Moreover, all level of feeding rate can support 100 % of survival rate. Efficient feed convertion ratio due to positive correlation with growth performance.  This study recommends feeding rate 13%/day may use as a point of standard operational procedure in grow-out business of spiny lobster.